High-fidelity simulation in Neonatology and the Italian experience of Nina - Armando Cuttano; Rosa Teresa Scaramuzzo; Marzia Gentile; Francesca Moscuzza; Massimiliano Ciantelli; Emilio Sigali; Antonio Boldrini (Journal of Pediatric and Neonatal Individualized Medicine, 2012)
The modern methodology of simulation was born in the aeronautical field. In medicine, anesthetists showed great attention for technological advances and simulation, closely followed by surgeons with minimally invasive surgery. In Neonatology training in simulation is actually useful in order to face unexpected dramatic events, to minimize clinical risk preventing errors and to optimize team work. Critical issues in simulation are: teachers-learners relationship, focus on technical and non-technical skills, training coordination, adequate scenarios, effective debriefing. Therefore, the quality of a simulation training center is multi-factorial and is not only related to the mannequin equipment. High-fidelity simulation is the most effective method in education. In Italy simulation for education in Medicine has been used for a few years only. In Pisa we founded Nina (that is the acronymous for the Italian name of the Center, CeNtro di FormazIone e SimulazioNe NeonAtale), the first neonatal simulation center dedicated but integrated within a Hospital Unit in Italy. This paper describes how we manage education in Nina Center, in order to offer a model for other similar experiences.